Heparin-dependent regulation of fibronectin matrix conformation - Hubbard, Brant (2013)
Extracellular matrix (ECM) conformation is regulated by a variety of stimuli in vivo, including mechanical forces and allosteric binding partners, and these conformational changes contribute to the regulation of cell behavior. Heparin and heparan sulfate, for example, have been shown to regulate the sequestration and presentation of numerous growth factors, including vascular endothelial growth factor, on the heparin 2 binding domain in fibronectin (Fn). However, mechanical force also alters Fn conformation, indicating that the growth factor binding region may be co-regulated by both heparin and mechanical force. Herein, we describe a simple antibody-based method for evaluating the conformation of the heparin 2 binding domain in Fn, and use it to determine the relative contributions of heparin and mechanical strain to the regulation of Fn conformation. We achieved specificity in quantifying conformational changes in this region of Fn by measuring the ratio of two fluorescent monoclonal antibodies, one that is insensitive to Fn conformational changes and a second whose binding is reduced or enhanced by non-equilibrium conformational changes. Importantly, this technique is shown to work on Fn adsorbed on surfaces, single Fn fibers, and Fn matrix fibers in cell culture. Using our dual antibody approach, we show that heparin and mechanical strain co-regulate Fn conformation in matrix fibrils, which is the first demonstration of heparin-dependent regulation of Fn in its physiologically-relevant fibrillar state. Furthermore, the dual antibody approach utilizes commercially available antibodies and simple immunohistochemistry, thus making it accessible to a wide range of scientists interested in Fn mechanobiology.